Genomic DNA extraction of Betta sp - Tan Azzri, bin Tan Smilly (Universiti Malaysia Sarawak (UNIMAS), 2016)
Berta sp. is a small fish which belongs to the family of Osphronemidae. The systematic status for Berta sp. is complex as it has a great diversity and it is difficult to differentiate their species. A study has been conducted to extract DNA from the muscle tissue, the scales and the liver of Berta ibanorum. A total of 15 individuals of Berta ibanorum have been obtained from Sungai Merah, Santubong. The extraction was done using five different methods. From the results obtained, CTAB method is the most effective method for extracting DNA from muscle tissue of Berta sp while phenol: chloroform method works better in extracting DNA from the scales of Berta sp. As for liver organ, commercial kit (Promega) has the highest mean of DNA concentration. PCR was also done using a set of primer targeting COI gene. DNA extracted using salting out method, CTAB method and commercial kit were more consistently amplified using PCR than boiling and phenol: chloroform-extracted DNA. Based on overall results, high concentration of DNA can be obtained from muscle tissue and scales. Therefore, it is recommended to use CTAB and phenol: chloroform method to extract DNA from Berta sp.